Xác định hằng số tốc độ và một số đại lượng nhiệt động của phản ứng OH• + HCNO bằng phương pháp lý thuyết - Nghĩa, Nguyễn Trọng; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
A theoretical investigation of the HCNO + ·OH reaction, which is carried out by means of B3LYP/6-311++G(3df,2p) + ZPVE computational method to determine a set of reasonable pathways. The potential energy surface for this system shows that there are sixteen different product pathways: PR1 (H2O + ·CNO), PR2 (CH2O + NO), PR3 (OCHNO + H), PR4 (CHOH: + NO), PR5 (CO2 + ·NH2), PR6 (HOCN + ·OH), PR7 (OCNOH + H), PR8 (HOCNO + H), PR9 (OCN· + H2O), PR10 (H2 + OCNO), PR11 (CO + ·NHOH), PR12(OCNH + ·OH), PR13 (CO + NO + H2), PR14 (·CHO + HNO), PR15 (CO + NH2O·) and PR16 (HCN + HO2·). The results indicate that PR11 (CO + ·NHOH) and PR14 (·CHO + HNO) are the major product channels. The rate constants for these processes have been calculated using variational RRKM theory covering the temperature range 300-1000 K and compared with available experimental data. The total rate constant of HCNO + ·OH reaction at 1atm, 300 K is 4.44´10-11 (cm3molecule-1s-1). Keywords: Kinetics, ·OH radical, forming CO, fulminic acid HCNO, potential energy surface (PES).